Science, Character, Elementary School: A Hybrid Systematic Literature Review and Bibliometric Analysis - Muhsinah Annisa; Teguh Prasetio; Fadhlan Muchlas Abrori; Herti Prastitasari; Mahmuddin Mahmuddin; Ifan Anom Bintoro Aji (Postgraduate, University of Mataram, 2026)
The integration of science learning and character education in elementary schools has increasingly attracted scholarly attention; however, the field lacks a comprehensive synthesis mapping its intellectual development, dominant themes, and methodological trajectories. This study aims to systematically examine publication trends, thematic structures, research designs, and emerging gaps in science–character integration at the elementary education level. A hybrid Systematic Literature Review (SLR) combined with bibliometric analysis was conducted on 51 Scopus-indexed articles published between 1997 and 2025. Article selection followed the PRISMA protocol, while co-occurrence and co-authorship analyses were performed using VOSviewer to identify conceptual and collaboration patterns. The findings demonstrate a marked growth in publications after 2018, with Southeast Asia as the primary contributor. Three major thematic clusters emerged: inquiry-based and literacy-oriented science learning, character value development emphasizing responsibility and religiosity, and integrative contextual pedagogical approaches. Quantitative experimental designs dominated the literature, primarily examining impacts on students’ motivation, conceptual understanding, and character formation, whereas longitudinal and mixed-method studies remain scarce. The review highlights the need for interdisciplinary and culturally responsive pedagogical frameworks capable of integrating scientific competencies and character development. This study provides an evidence-based reference for researchers and educators seeking to advance holistic science education in elementary schools.